Motivations and attitudes of undergraduate students toward ESP classes in an Egyptian university - Ali, Waleed Emad (AUC Knowledge Fountain, 2014)
In the last few decades, English for Specific Purposes (ESP) has become one of the most needed sub-fields of English for Speakers of Other Languages (ESOL). In Egypt, ESP courses are widely taught in both public and private universities. Also, motivation and attitude play an essential role in how well a learner understands the suggested material in an educational environment. They are considered important factors which may have an effect on the ESP educational process in Egypt. Many studies have addressed the area of motivation and attitudes in the EFL context. However, after a thorough review of the literature available on this subject, there appears to be a scarcity in the research on ESP students' motivations and attitudes in the Egyptian context. Based on the researcher's 10 years of experience teaching ESP classes in addition to conducting a pilot study, there is a need for a study concerning ESP learners' motivation and attitudes in Egypt. This study focuses on the motivations and attitudes of students in ESP classes in various academic years at a public university, Mansoura University. The study was guided by three research questions. The first investigated the types of motivation the students have when taking ESP classes and how much they are motivated toward them. The second explored the attitudes of undergraduate students toward ESP courses at Mansoura University. The third investigated whether students' academic disciplines affect their motivation and attitudes toward ESP courses. The study adopted a mixed-methods exploratory applied design. The research involved 517 participants of non-English majors who were registered in undergraduate ESP courses in the 2014 spring semester at Mansoura University. Both quantitative and qualitative data were collected through their responses to a 4-point Likert scale questionnaire, multiple-choice format scales, open-ended questions, and a semi-structured interview. The results of the study showed that students are motivated both intrinsically and extrinsically in addition to having high motivational intensity and a deep interest toward ESP classes. The study also revealed that the students have a relatively positive attitude toward their ESP courses. However, there are several factors that affect the students' attitudes such as unrelated course materials, inconvenient course schedules, lack of incorporation of educational technology into classroom instructions, poor teaching methods of the professors and instructors, or the learning environment that affect the students' attitudes negatively. In addition, the results showed that the academic discipline is not considered an important factor that affects students' motivation toward their ESP classes. However, a slight positive trend in the attitude of ESP students was shown in the present study which may arise from different conditions regarding the students' goals and the conditions of different classes at different academic disciplines. The implications of this study may help the universities develop ESP courses in order to increase ESP students' motivation and attitudes toward their ESP classes.